Current State and Objectives of The Industry for Improving Oil Field Development Systems with Waterflooding - Navruz Khushmuradovich Ermatov; Samatov Sherzod Shavkatovich; Bekjonov Rozisher Soatmuradovich; Bazarov Ulugbek Suyun ogli (Scientific Trends, 2025)
This article is devoted to the current state and tasks of improving the systems of development of the Fergana oil fields with waterflooding. The authors consider such issues as the history of the development of waterflooding methods, various waterflooding systems and the conditions for their application, the density of the production well grid, the pressure drop between the injection line and the production zone, the approach to the development of water-oil zones, the sequence of commissioning injection wells, regulation and intensification of production, ways to improve the efficiency of developing multilayer objects. The article also analyzes the practical results and future prospects of waterflooding in the Fergana fields.
Keywords: Oil field, Waterflooding, Development system, Oil recovery factor, Reservoir pressure, Well grid, Injection well, Multilayer object, Production regulation, Fergana.